Automated system for the creation and replenishment of users' electronic lexicographical resources - Borysova, N. V.; Melnyk, K. V. (Society for Cultural and Scientific Progress in Central and Eastern Europe, 2018)
This article proposes a solution to improve the efficiency of automated generation of electronic lexicographical resources based on strongly-structured electronic information arrays processing. The developed automated information system for lexicographical resources creation and replenishment have been described is this article. Several supporting subsystems of developed automated system have been characterized. The effectiveness of the information system has been evaluated.
Keywords: automated systems; natural language processing; electronic lexicographical resources; strongly-structured electronic information arrays